(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In article questions of improvement of vocational training of the future teachers through purposeful de velopment of methodological culture are brought up; the content and essence of methodological culure of the future teacher is considered; approaches purposeful to formation and developments in the conditions of profes sional formation are allocated.